2015
DOI: 10.1111/bij.12614
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic analyses reveal distinct geographical blooms of the jellyfishRhizostoma octopus(Scyphozoa)

Abstract: Understanding the spatial integrity and connectivity of jellyfish blooms is important for ecologists and coastal stakeholders alike. Previous studies have shown that the distribution of jellyfish blooms can display a marked consistency in space and time, suggesting that such patterns cannot be attributed to passive processes alone. In the present study, we used a combination of microsatellite markers and mitochondrial cytochrome oxidase I sequences to investigate genetic structuring of the scyphozoan jellyfish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 79 publications
(84 reference statements)
2
10
0
Order By: Relevance
“…1.5 Mya), thus ruling out recent episodes of glaciation as the causal factor in promoting divergence. Furthermore, the palaeodistribution model suggests the persistence of a large, continuous population of P. noctiluca during the LGM, similar to the scenario observed in the zooplankton Calanus finmarchicus (Provan et al ., ), but in contrast to our earlier findings in the metagenic jellyfish Rhizostoma octopus (Glynn et al ., ). The fact that individuals from both the Atlantic and the Mediterranean are represented by haplotypes from each clade, coupled with the observed lack of any structuring in the microsatellite data set, further suggests extensive admixture since the divergence of the two clades.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…1.5 Mya), thus ruling out recent episodes of glaciation as the causal factor in promoting divergence. Furthermore, the palaeodistribution model suggests the persistence of a large, continuous population of P. noctiluca during the LGM, similar to the scenario observed in the zooplankton Calanus finmarchicus (Provan et al ., ), but in contrast to our earlier findings in the metagenic jellyfish Rhizostoma octopus (Glynn et al ., ). The fact that individuals from both the Atlantic and the Mediterranean are represented by haplotypes from each clade, coupled with the observed lack of any structuring in the microsatellite data set, further suggests extensive admixture since the divergence of the two clades.…”
Section: Discussionmentioning
confidence: 97%
“…From a molecular perspective most studies of population structure in P. noctiluca to date, and indeed jellyfish in general (reviewed in Glynn, Houghton & Provan, 2015), have relied heavily on the mitochondrial cytochrome oxidase I (COI) gene, occasionally with the addition of ribosomal markers such as the internal transcribed spacers ITS1 and ITS2 (e.g. Stopar et al, 2010).…”
mentioning
confidence: 99%
“…Mitochondrial DNA only retains half of the species' evolutionary history (Avise 2000), and due to the potential differential selection (Silva et al 2014;Consuegra et al 2015) and stochasticity of the coalescence processes between nuclear and mitochondrial DNA, these two types of markers can show different evolutionary signatures (e.g. Glynn et al 2015;Garcia-Cisneros et al 2016;Pérez-Portela et al 2017). Therefore, combining both mitochondrial and nuclear information should provide complementary information to unravel both recent and historical processes shaping the genetic structure of A. lixula.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Bastian et al (2014) showed that the allometric relationship for three jellyfish species in the Irish Sea was different when compared to other studies; they also found significantly different average mass per individual between the western and the eastern regions of the Irish Sea, presumably due to the different food environments. Recent studies found that the different R. octopus populations around the United Kingdom and France were genetically distinct (Lee et al, 2013;Glynn et al, 2015). Glynn et al ( 2015) presented further evidence that the populations in Carmarthen Bay, Celtic Sea, Tremadoc Bay and Solway Firth originated from a single population but are geographically separated after the last glacial maximum, which may explain the different allometric relationships between the populations.…”
Section: Discussionmentioning
confidence: 79%
“…Recent studies found that the different R. octopus populations around the United Kingdom and France were genetically distinct (Lee et al, 2013;Glynn et al, 2015). Glynn et al ( 2015) presented further evidence that the populations in Carmarthen Bay, Celtic Sea, Tremadoc Bay and Solway Firth originated from a single population but are geographically separated after the last glacial maximum, which may explain the different allometric relationships between the populations. Further comparison of the allometric relationships among the different populations will prove useful, especially if the R. octopus fishery expands to the other areas.…”
Section: Discussionmentioning
confidence: 79%